Cover Picture: Virtual Screening Based on Ensemble Docking Targeting Wild‐Type p53 for Anticancer Drug Discovery (C&B 7/2019). Issue 7 (25th June 2019) - Li, Xin; Zhang, Xin‐Xin; Lin, Yu‐Xi; Xu, Xi‐Ming; Li, Li; Yang, Jin‐Bo
Abstract : Cover Picture . In this study, virtual screening is introduced to identify natural products targeting the wild‐type p53 Loop1/Sheet3 pocket. This pocket contains Cys124 site and is reported to be important to stabilize and reactive mutant p53. Considering of the high flexibility of Loop1, ensemble docking method is utilized to obtain druggable conformation of L1/S3 pocket for docking. As one of the selected candidates through virtual screening, torilin is then proved to bind to Cys124 of p53 by the 2‐methyl‐2‐butenal group, increases the p53 transcription activity and activates the p53 pathway to suppress cancer cell growth as reported by X. Li et al . in their full paper at10.1002/cbdv.201900170 .